2019
DOI: 10.1136/bmjopen-2018-026920
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin and heparin for the prevention of pre-eclampsia: protocol for a systematic review and network meta-analysis

Abstract: IntroductionPre-eclampsia is an important cause of death and complication for pregnant women and perinatal infant. Low-dose aspirin has been most commonly used to prevent pre-eclampsia in high-risk pregnant women. Recently, heparins have also been used alone or in combination with aspirin to prevent pre-eclampsia. However, the optimal doses and combination therapy of aspirin and heparins are not well established. Therefore, we aim to compare aspirin, heparins and their combination to prevent pre-eclampsia in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The main mechanism of action of aspirin is that it reduces endothelial cell injury and inhibits platelet aggregation and thrombosis, thereby having antihypertensive and anticoagulant effects [35,36]. Aspirin at a low dose does not increase the incidence of maternal thrombocytopenia, maternal postpartum hemorrhage, or prenatal and postpartum hemorrhage, nor does it increase the bleeding tendency and neonatal disease rate of the newborns; therefore, oral administration of low-dose aspirin during pregnancy is relatively safe for mothers and infants [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…The main mechanism of action of aspirin is that it reduces endothelial cell injury and inhibits platelet aggregation and thrombosis, thereby having antihypertensive and anticoagulant effects [35,36]. Aspirin at a low dose does not increase the incidence of maternal thrombocytopenia, maternal postpartum hemorrhage, or prenatal and postpartum hemorrhage, nor does it increase the bleeding tendency and neonatal disease rate of the newborns; therefore, oral administration of low-dose aspirin during pregnancy is relatively safe for mothers and infants [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] LMWH can combine with anticoagulant live enzymes AT. The inhibition of AT on FXa and thrombin is enhanced, [ 9 ] while the influence on platelet counts is small. Several clinical trials [ 25 26 ] have demonstrated that LMWH is beneficial for improving pregnancy outcomes in pregnant women with severe PE, fetal growth restriction, and thrombotic tendency.…”
Section: Discussionmentioning
confidence: 99%
“…It is gradually recognized clinically by blocking the malignant process of coagulation reaction. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, we will use the data available to us, but the potential impact of them will be addressed in the assessment of risk of bias. If we cannot get the reply from authors, the data will be verified from other trials in the network or from other published meta-analyses 47 48…”
Section: Methodsmentioning
confidence: 99%